The Preservation of the Asian-African Conference Museum Library Collections - Oktavia, Nurul; CMS, Samson (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
The Asian African Conference Museum owns a special library that has stored a variety of rare collections, especially collections on the holding of the 1955 Asian African Conference. This study aims to describe the preservation carried out by the library for those rare collections. The research used a descriptive qualitative method. The data were obtained through interviews with the staff of the Asian African Conference Museum Library, and literature studies. The result showed that the Asian African Conference Museum Library had preserved the collection by limiting visitors to the collection room, cleaning the dust using a vacuum cleaner, using shelves according to standards, cooperating with the National Library of the Republic of Indonesia in restoration, and implementing a ban on visitors carrying food/drink to the library. However, there were still many efforts that need to be implemented and optimized such as temperature and humidity control, lighting, pollution, prevention of insects and fungi, and anticipate natural disasters. The role of the librarian is needed to optimize the preservation of collection efforts in the Asian African Conference Museum Library.